PENGARUH ETOS KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI KECAMATAN SEI. KIJANG KABUPATEN PELALAWAN - Misroji, Misroji; Saam, Zulfan; Isjoni, Isjoni (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2022)
This study aims to (1) find out that work ethic affects teacher performance, (2) organizational climate affects teacher performance, (3) work ethic and organizational climate affect teacher performance together. The respondents to the study were teachers of State Elementary Schools in Sei Kijang Subdistrict, Pelalawan Regency, totaling 163 people with a sample of 116. Data collection is carried out through the dissemination of questionnaires. The data analysis used is descriptive analysis, inferential statistical analysis. The reliability coefficient of the instrument is calculated using the cronbach alpha formula. The results showed that there was a positive and significant influence of work ethic on teacher performance of 0.621, and there was a positive and significant influence of the organizational climate on teacher performance of 0.433. Meanwhile, together there is an influence of work ethic and organizational climate on teacher performance of 0.650.